Nano-ZnO decorated ZnSnO3 as efficient fillers in PVDF matrixes: toward simultaneous enhancement of energy storage density and efficiency and improved energy harvesting activity. Issue 40 (14th October 2020) - Sasmal, Abhishek; Medda, Samar Kumar; Devi, P. Sujatha; Sen, Shrabanee
Abstract : Along with enhanced dielectric permittivity and suppressed dielectric loss, PVDF-ZnO@ZnSnO3  films showed simultaneous enhancement in electrical energy storage density and storage efficiency compared to PVDF-ZnSnO3  composites. Abstract : Here, we report the effect of ZnO decoration on ZnSnO3  fillers on the dielectric property, energy storage behaviour and mechanical energy harvesting performance of PVDF matrixes. More enhanced dielectric constant and reduction in dielectric loss were achieved in PVDF–ZnO@ZnSnO3 (PVDF–ZNZS) films than in PVDF–ZnSnO3 (PVDF–ZS) films for the same concentration of filler loading. Similarly, PVDF–ZNZS films showed simultaneous enhancement in electrical energy storage density and storage efficiency compared to PVDF–ZS composites. As all the constituent materials (PVDF, ZnSnO3 and ZnO) were piezoelectric, the resulting composite film showed improved piezoelectric energy harvesting performance too. After rectification, the output ac voltage was used to charge a 10 μF capacitor up to ∼5 V dc which was further used to light up some LEDs. Furthermore, in order to exhibit improved sensitive output, a hybrid piezo-tribo nanogenerator was fabricated which was demonstrated as a motion sensor, a weight sensor and a human body movement sensor as part of a real life application.